The principles of conservation and development: do they apply in Malinau? - Boedhihartono, Agni K.; Gunarso, Petrus; Levang, P.; Sayer, Jeffrey A. (2007)
Attempts to reconcile economic development with environmental conservation in a forest area in East Kalimantan, Indonesia, are reviewed for the district of Malinau, East Kalimantan, Indonesia, an area of 42,000 km2 that is still largely covered in rainforest. The history of the region is described and the conservation and development impacts of external drivers of change are assessed. Both government and conservation organizations have subscribed to the rhetoric of pursuing development pathways that would be sustainable and would conserve the rich biodiversity of the area. Three distinct approaches to conservation have been attempted. First spatial planning has been used to attribute land to different uses and particularly to identify and designate protected areas. Second, measures have been taken to lessen the negative environmental impact of industrial logging and to promote the preservation of biodiversity in logged forests. Last, decentralized and community-based management has been promoted on the assumption that this would yield better environmental and social outcomes than large-scale industrial development. These conservation measures have been pursued during a period when the governance of the region has been weak. Corruption, political collusion, and nepotism have been major factors in decision making about natural resources. We argue that a sustainable future for the district of Malinau must lie in finding an appropriate balance between protected areas, forests managed at both industrial and community scales, and land conversion. However, there is little empirical evidence that allows the outcomes of these approaches to be measured. The problem of knowing how conservation investments can be made in ways that optimize sustainable benefits to local livelihoods remains largely unresolved. A number of possible conservation and development pathways for the district are discussed.